Zellweger syndrome; identification of mutations in PEX19 and PEX26 gene in Saudi families - Abdulfatah M. Alayoubi; Ambreen Ijaz; Abdul Wali; Jamil A. Hashmi; Azizah Alharbi; Sulman Basit (Annals of Medicine)
Background Peroxisome biogenesis disorders (PBD) affect multiple organ systems. It is characterized by neurological dysfunction, hypotonia, ocular anomalies, craniofacial abnormalities, and absence of peroxisomes in fibroblasts. PBDs are associated with mutations in any of fourteen different PEX genes, which are involved in peroxisome biogenesis. Zellweger spectrum disorder (ZSD) is a severe form of PBD. More than 90% of the ZSD cases have mutations in PEX1, PEX6, PEX10, PEX12, and PEX26. Mutations in the PEX19 gene are rarely associated with PBD/ZSD; however, a large proportion of PEX26 mutations are associated with ZSD.Methods We recruited two Saudi families with multiple affected individuals with dysmorphic features, including hypertelorism, large open fontanelles, generalized hypotonia, and epicanthal folds with poor reflexes since birth. Whole exome sequencing (WES) and Sanger sequencing was performed to identify the genetic cause. The frequency and pathogenicity of the identified mutations were assessed using various online bioinformatics tools.Results WES identified a novel nonsense variant (c.367C > T) in the PEX19 gene in family A patients. This nonsense mutation was predicted to cause premature termination (p.Gln123*). A previously reported synonymous variant (c.228C > T; p.Gly76Gly) in PEX26 was found in a patient from family B. Both variants were segregating in an autosomal recessive manner in the respective families.Conclusion The present study has added a novel nonsense mutation to the mutation spectrum of PEX19, which is the second null mutation identified to date. Moreover, in this study, the importance of a synonymous exonic variant of PEX26 close to the splice donor site was explored in relation to pre-mRNA splicing and resulting disease manifestations.